2017
DOI: 10.1590/s1808-185120171604183510
|View full text |Cite
|
Sign up to set email alerts
|

The Etiologic Relevance of 3-D Pathoanatomy of Adolescent Idiopathic Scoliosis

Abstract: Despite many years of dedicated research into the etiopathogenesis of adolescent idiopathic scoliosis, there is still no single distinct cause for this puzzling condition. In this overview, we attempt to link knowledge on the complex three-dimensional pathoanatomy of AIS, based on our ongoing research in this field, with etiopathogenic questions. Evidence from multiple recent cross-sectional imaging studies is provided that supports the hypothesis that AIS has an intrinsic biomechanical basis: an imbalance bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
2
0
0
Order By: Relevance
“…11,30 Newer investigations have suggested that anterior overgrowth and overall scoliotic lordosis may be a more generalized deformity observed across all forms of scoliosis. 27,31 These correlation findings, in conjunction with the static local lordosis described previously, support a relationship between progression of coronal curvature and axial rotation, but not with sagittal kyphosis/lordosis.…”
Section: Deformitysupporting
confidence: 80%
See 1 more Smart Citation
“…11,30 Newer investigations have suggested that anterior overgrowth and overall scoliotic lordosis may be a more generalized deformity observed across all forms of scoliosis. 27,31 These correlation findings, in conjunction with the static local lordosis described previously, support a relationship between progression of coronal curvature and axial rotation, but not with sagittal kyphosis/lordosis.…”
Section: Deformitysupporting
confidence: 80%
“…This is of particular interest because the concept of asynchronous anterior overgrowth that produces the characteristic lordosis of the thoracic scoliotic spine had been previously suggested as an etiological driver of AIS deformity 11,30 . Newer investigations have suggested that anterior overgrowth and overall scoliotic lordosis may be a more generalized deformity observed across all forms of scoliosis 27,31 . These correlation findings, in conjunction with the static local lordosis described previously, support a relationship between progression of coronal curvature and axial rotation, but not with sagittal kyphosis/lordosis.…”
Section: Discussionsupporting
confidence: 57%